Impact of a syndrome-specific antibiotic stewardship intervention on antipseudomonal antibiotic use in inpatient diabetic foot infection management - Randy J. McCreery; Elizabeth Lyden; Matthew Anderson; Trevor C. Van Schooneveld (Cambridge University Press, 2023)
Abstract Objective: To demonstrate that a syndromic stewardship intervention can safely reduce antipseudomonal antibiotic use in the treatment of inpatient diabetic foot infections (DFIs). Intervention and method: From November 2017 through March 2018, we performed an antimicrobial stewardship intervention that included creation of a DFI best-practice guideline, implementation of an electronic medical record order set, and targeted education of key providers. We conducted a retrospective before-and-after study evaluating guideline adherent antipseudomonal antibiotic use 1 year before and after the intervention using interrupted time-series analysis. Setting: University of Nebraska Medical Center, a 718-bed academic medical center in Omaha, Nebraska. Patients: The study included 193 adults aged ≥19 years (105 in the preintervention group and 88 in the postintervention group) admitted to non-intensive care units whose primary reason for antibiotic treatment was diabetic foot infection (DFI). Results: Guideline-adherent use of antipseudomonal antibiotics increased from 39% before the intervention to 68% after the intervention (P ≤ .0001). Antipseudomonal antibiotic use decreased from 538 days of therapy (DOT) per 1,000 DFI patient days (PD) before the intervention to 272 DOT per 1,000 DFI PD after the intervention (P < .0001), with a statistically significant decrease in both level of use and slope of change. We did not detect any changes in length of stay, readmission, amputation rate, subsequent positive Clostridioides difficile testing, or mortality. Conclusions: Our 3-component intervention of guideline creation, implementation of an order set, and targeted education was associated with a significant decrease in antipseudomonal antibiotic use in the management of inpatient DFIs. DFIs are common and should be considered as opportunities for syndromic stewardship intervention.